Sociocultural approach to regulation of inter-ethnic relations - Yuri V. Popkov; Evgenyi A. Tyugashev (Novye Issledovaniâ Tuvy, 2016)
In this article the content of sociocultural approach is explicated. On the examples of the local communities of Khanty-Mansiysk (Ugra) and Yamalo-Nenets autonomous okrugs the methodological possibilities of sociocultural approach in regulation of inter-ethnic relations are illustrated.